Ipsilateral transfer of motor skill from upper to lower limb in healthy adults: a randomized controlled trial - Elion, Orit; Kozol, Zvi; Einat, Moshe; Frenkel-Toledo, Silvi (Frontiers in Human Neuroscience, 2025)
Intermanual transfer refers to the improvement of motor skill in an untrained contralateral limb following unilateral limb practice. However, it remains uncertain whether motor skill in the lower limb (LL) can improve as a result of practice with the unilateral upper limb (UL). Forty-five healthy participants were randomly allocated to one of three groups: (1) UL group, which practiced reaching movement (RM) sequences with the non-dominant left upper limb; or (2) switches observation (SO) group, which observed the same RM sequences; or (3) nature observation (NO) group, which observed nature movies. RM performance with the LL was assessed before, immediately after, and 24 h post-intervention. Response time of RM sequences was faster in the UL group than the NO group in the posttest. Response time improved significantly in the posttest and retest compared to the pretest in all groups, but it improved significantly in the retest compared to the posttest only in the NO group. The percentage of fails to reach within 1 s decreased across all time points in all groups. The combination of practice of the RM sequence with the UL and the cognitive engagement during RM sequence observation contributes to ipsilateral transfer from the UL to the LL.